Método POLYA en la resolución de problemas de combinación en estudiantes del 5to grado de educación primaria Cotay- Churcampa 2021 - Arreguela Llancari, Denis Yeferson (2025)
The research addressed the general problem of deficient problem-solving skills in combination problems among fifth-grade students at Educational Institution No. 30980 in the rural community of Cotay during 2021. The main objective was to evaluate the didactic value of Pólya’s method in overcoming this difficulty. The study population consisted of 65 students, a sample of 15 was selected. The methodological approach was applied in nature and explanatory in level, employing a pretest-posttest design with a single group. The scientific method was utilized, with extensive direct observation as the technique and the "Mathematics Written Test Questionnaire" as the instrument. Results indicated that 66.7% of students achieved a level above expectations in solving combination problems, demonstrating significant improvement in the post-test compared to the pre-test. It is concluded that Pólya’s method significantly contributed to optimizing problem-solving skills in combination problems among the participating students